(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the linguocultural features of axiological vocabulary in English and Uzbek languages. The study focuses on lexical units that express social, moral, and cultural values and analyzes their semantic and linguocultural characteristics. Particular attention is given to how values are reflected in language through evaluative vocabulary and how these units are shaped by historical, cultural, and social factors. The article also highlights the similarities and differences in the representation of values in the lexical systems of English and Uzbek. The findings demonstrate that axiological vocabulary plays an important role in reflecting national mentality, cultural traditions, and value systems of different linguistic communities.